2017
DOI: 10.1017/s0714980817000411
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing New RNs’ Supervisory Performance in Long-Term Care Facilities

Abstract: In long-term care facilities (LTCF), registered nurses (RNs) perform both clinical and supervisory roles as part of a team aiming to provide high-quality care to residents. The residents have several co-morbidities and complex care needs. Unfortunately, new RNs receive minimal preparation in gerontology and supervisory experience during their program, leading to low retention rates and affecting resident outcomes. This qualitative study explored factors that influence supervisory performance of new RNs in LTCF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 21 publications
0
22
1
Order By: Relevance
“…In contrast to previous studies focusing on the RNs' supervisory skills and the difficulties they experienced as supervisors (McGilton et al, ; Prentice et al, ), findings from this study revealed the multiple additional responsibilities RNs hold as charge nurses in LTCFs. The role of the charge nurse in LTCFs is essential to patient safety, workforce organisation and regulatory compliance.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In contrast to previous studies focusing on the RNs' supervisory skills and the difficulties they experienced as supervisors (McGilton et al, ; Prentice et al, ), findings from this study revealed the multiple additional responsibilities RNs hold as charge nurses in LTCFs. The role of the charge nurse in LTCFs is essential to patient safety, workforce organisation and regulatory compliance.…”
Section: Discussioncontrasting
confidence: 99%
“…There should be an acknowledgement that a certain level of experience is required to meet the demands placed upon charge nurses by the multiple dimensions and responsibilities of this role. We may be setting charge nurses up for failure and jeopardising their health by recruiting new graduates for this role, which may lead to deleterious effects on resident outcomes (Prentice et al, ), the work environment and staff outcomes (Escrig‐Pinol et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations